Effect and mechanism of miRNA-144-5p-regulated autophagy in older adults with Sarcopenia - Mengdie Hu; Ying Zhang; Hong Ding; Rui Chao; Zhidong Cao (Immunity & Ageing, 2025)
Abstract Background Advanced aging invariably triggers an overabundance of apoptosis, stemming from diminished autophagy or a disarray in cellular autophagic processes. This, in turn, leads to an accelerated breakdown of muscle proteins, which exacerbates the ongoing deterioration of skeletal muscle and intensifies the severity of senile sarcopenia. This study aimed to investigate the role and mechanism of miRNA-regulated autophagy in senile sarcopenia. Methods The miRNAs associated with sarcopenia were screened, and the target genes of significant miRNAs were predicted. The effects of significantly differentially expressed miRNA-144-5p on cell aging and autophagy were validated in vivo and in vitro. Results The inhibition of miR-144-5p enhanced the multiplication of mouse myoblasts, increased the expression of MHC and autophagic markers LC3II/LC3I and Beclin-1, facilitated the formation of autophagosomes in mouse myoblasts, and reduced the number of aging cells and the expression of senescence-related proteins acetylated p53, p53, and p21 expression in mouse myoblasts. miR-144-5p affects myoblast senescence, myogenic differentiation, and autophagy by regulating the downstream target gene, Atg2A. Inhibiting miR-144-5p markedly increased the grip strength of the posterior limb in old mice, and the CSA of old mice and young mice was also markedly increased. Conclusion All experiments have demonstrated that miRNA-144-5p has a significant impact on the regulation of autophagy and the development of senile sarcopenia.